Training and Manufacturing Assistance Digital-Based Picture Stories for Teachers Kindergarten/PAUD ABA III Rewwin - Siti Rahayu Nasichatu Muslimatin; Siti Latifatus Sun'iyah (Shof Journal of Social Impact, 2024)
This service aims to provide training and assistance in creating digital-based picture stories for ABA III Rewwin Kindergarten/PAUD teachers.  This effort is part of an effort to increase digital literacy and skills for teachers to be more creative and innovative in creating learning media. This activity is expected to increase teacher competence in creating digital-based learning media. This training is in collaboration with TK/PAUD ABA III Rewwin Waru Sidoarjo, which can be seen from the implementation of teacher skills in creating digital illustrated stories. The output of this training and mentoring is expected to be in the form of improving the quality of education and the potential for publication of research results and can contribute positively in facing educational challenges in the digital era.